PERAN ORANGTUA DALAM MEMOTIVASI ANAK UNTUK MEMANFAATKAN INTERNET SEBAGAI MEDIA PEMBELAJARAN - Suryani, Suryani (Universitas Esa Unggul, 2018)
AbstractThis community service aims to provide knowledge to the public about the importance of the internet as a learning medium for the success of children's. So that the role of parents is needed to succeed this. This community service is imposed on the people of Palumbonsari, East Karawang. education. This community service is imposed on the people of Palumbonsari, East Karawang. The method of implementation is to conduct counseling to the people of Palumbonsari and then do a question and answer session between the presenter and participants. With the existence of this community service, it is expected that the community understands the importance of the internet as a learning medium so that children can be motivated to study hard.Ã‚Â Keywords : role of parents, internet, motivationÃ‚Â AbstrakPengabdian masyarakat ini bertujuan untuk memberikan pengetahuan kepada masyarakat tentang pentingnya internet sebagai media pembelajaran guna keberhasilan pendidikan anak. Sehingga peran orangtua dibutuhkan untuk mensukseskan hal tersebut. Pengabdian masyarakat ini dikenakan kepada masyarakat Palumbonsari, karawang Timur.Adapun metode pelaksanaannya adalah melakukan penyuluhan kepada masyarakat Palumbonsari dan kemudian dilakukan tanya jawab antara presenter dan peserta. Dengan adanya pengabdian masyarakat ini diharapkan masyarakat memahami pentingnya internet sebagai media pembelajaran sehingga anak dapat termotivasi untuk belajar lebih giat lagi.Ã‚Â Kata kunci: peran orangtua, internet, motivasiÃ‚Â